2005
DOI: 10.1038/sj.npp.1300794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SCH-23390 Infused into the Amygdala or Adjacent Cortex and Basal Ganglia on Cocaine Seeking and Self-Administration in Rats

Abstract: Amygdala D1 receptors have been implicated in the motivating effects of cocaine-conditioned cues and cocaine itself, but the specific nucleus involved is unclear. Thus, we infused the D1 antagonist, SCH-23390, into the rostral basolateral amygdala (rBLA), caudal basolateral amygdala (cBLA), or central amygdala (CEA), and tested its effects on self-administration of cocaine, as well as reinstatement of extinguished cocaine-seeking behavior by cocaine-conditioned cues or cocaine itself. Two anatomical controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 74 publications
(95 reference statements)
6
47
1
Order By: Relevance
“…The disparity between our results and those of Bachtell et al (2005) for food self-administration likely reflect differences in the type of operant schedule used (FI5(FR5:S) versus FR1) and the brain region targeted. Moreover, it should be noted that the doses of SCH 23390 used in the current study are quite high and, as pointed out by others (Alleweireldt et al 2006), any changes in behavior may reflect interactions with additional receptors in the AId such as 5-HT 2C receptors (Millan et al 2001) and G proteincoupled, inwardly rectifying potassium channels (Kuzhikandathil and Oxford 2002) for which SCH-23390 has an affinity. Given that SCH 23390 is a potent agonist at 5-HT 2C receptors (Millan et al 2001) and that 5-HT 2C agonists have been shown to reduce food-maintained responding in squirrel monkeys (Brady and Barrett, 1985;McKearney, 1990), this may be why infusion of SCH 23390 but not SKF 81297 led to global disruptions in operant responding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The disparity between our results and those of Bachtell et al (2005) for food self-administration likely reflect differences in the type of operant schedule used (FI5(FR5:S) versus FR1) and the brain region targeted. Moreover, it should be noted that the doses of SCH 23390 used in the current study are quite high and, as pointed out by others (Alleweireldt et al 2006), any changes in behavior may reflect interactions with additional receptors in the AId such as 5-HT 2C receptors (Millan et al 2001) and G proteincoupled, inwardly rectifying potassium channels (Kuzhikandathil and Oxford 2002) for which SCH-23390 has an affinity. Given that SCH 23390 is a potent agonist at 5-HT 2C receptors (Millan et al 2001) and that 5-HT 2C agonists have been shown to reduce food-maintained responding in squirrel monkeys (Brady and Barrett, 1985;McKearney, 1990), this may be why infusion of SCH 23390 but not SKF 81297 led to global disruptions in operant responding.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that intra-cranial infusion of SCH 23390 within the medial PFC (0.3 μg/ side), NAc shell (1.0 μg/side), or BLA (2.0 μg/side) reduces drug-seeking behavior induced by cocaine-associated cues or a priming injection of cocaine (See et al 2001;Bachtell et al 2005;Sun and Rebec 2005;Berglind et al 2006), whereas infusion into the caudal BLA (2.0 μg/side) or NAc shell (1.0 μg/side) significantly increases the number of cocaine infusions earned during maintenance testing (Alleweireldt et al, 2006;Bachtell et al 2005). In the present study however, intra-AId infusions with similar doses of SCH 23390 (i.e., 1.0 and 2.0 mg/side) did not yield any significant findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, although dopaminergic input from the VTA to the OFC controls neuronal activity (Aou et al, 1983), back-projections from the OFC to the VTA may also regulate dopaminergic input to the OFC itself and to the BLA (Takahashi et al, 2009). In particular, input from the VTA to the BLA may be important for processing the motivational effects of cocaine-paired contextual stimuli, given that dopamine D1-like receptor antagonism in the BLA prevents explicit drug-paired cues from eliciting cocaineseeking behavior (Alleweireldt et al, 2005;Berglind et al, 2006;Mashhoon et al, 2009;See et al, 2001).…”
Section: Discussionmentioning
confidence: 99%